Hot Air for Sale: A Quantitative Assessment of Russia's Near-Term Climate Policy Options - Christoph Böhringer; Ulf Moslener; Bodo Sturm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Since January 1st the European Union has launched an EU-internal emissions trading scheme (EU ETS) for emission-intensive installations as the central pillar to comply with the Kyoto Protocol. The EU ETS may be linked at some time to a Kyoto emissions market where greenhouse gas emission allowances of signatory Kyoto countries can be traded. In this paper we investigate the implications of Russian market power for environmental effectiveness and regional compliance costs to the Kyoto Protocol taking into account potential linkages between the Kyoto emissions market and the EU ETS. We find that Russia may have incentives to join the EU ETS as long as the latter remains separated from the Kyoto international emissions market. In this case, Russia can exert monopolistic price discrimination between two separated markets thereby maximizing revenues from hot air sales. The EU will be able to substantially reduce compliance costs when it does not restrain itself to EU-internal emission regulation schemes. However, part of the gains from extra-EU emissions trading will come at the expense of environmental effectiveness as (more) hot air will be drawn in.
Keywords: Q25; D42; 330; market power; hot air; climate policy; Klimaschutz; Emissionshandel; Emissionsrechte; EU-Europäisch; Marktmacht; Russland